Faktor-Faktor Psikologis yang Berhubungan dengan Kejadian Hiperemesis Gravidarum di Rumah Sakit Harapan dan Doa Kota Bengkulu - Khariza Fadhila Syahnaz; Lidwina Trieleventa Lumruan Sihombing (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Hyperemesis gravidarum is the frequency of nausea and vomiting in pregnant women up to more than 10 times per day which can affect the general condition and hinder daily activities.The purpose of this study was to find out in-depth information about psychological factors related to the incidence of hyperemesis gravidarum in Harapan dan Doa Hospital of Bengkulu City. This study uses descriptive research design with qualitative methods. Data collection is based on in-depth interviews. Taking research subjects using purposive sampling technique. The main informants consisted of 5 pregnant women who experienced gravidarum hyperemesis and secondary informants consisting of husbands, families of pregnant women, and midwives. The results showed that most mothers received less pregnancy. A small number of informants lacked husband's support. There are pregnant women who lack family support. Most housewives and 1 who work experience stress in work. Health workers are expected to conduct prenatal counseling in first trimester pregnant women, so that pregnant women know the symptoms that lead to hyperemesis gravidarum and timely consultation with health workers, and also can monitor the psychological state of pregnant women that can affect their pregnancy